Model Pembelajaran Dengan Pendekatan STEAM Berbantuan Aplikasi Pixton dan Quizizz Untuk Meningkatkan Berpikir Kritis - Rahmawati, Rahmawati (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to determine students’ critical thinking ability in using STEM Methods with pixton and Quizizz applications in Algebra Multiplication material in grade VIII MTs.Al-Hilaliyah Palembang. This research is descriptive research with the subject of the study being class VIII totaling 35 students. Data collection is carried out through test instruments in the form of descriptions that have gone through the validation test stage. To measure students’ ability to think critically, 4 indicators are used, namely: 1) Problem identification, 2) Analysis, 3) Problem solving, and 4) Drawing conclusions. The research shows that the critical thinking ability of students in the MTs Al-Hilaliyah Palembang class after participating in the learning process using interactive multimedia is classified as moderate with a percentage of 71.5%. Of the 35 respondents, only 20 students were in the very high category, 5 students were in the high category, 4 students were in the medium category, 4 students were in the low category and 2 students were in the very low category. Judging from each indicator of students’ critical thinking skills, including problem identification obtained a percentage of 72.92%, analysis obtained a percentage of 64.58%, solving problems obtained a percentage of 63.89% and drawing conclusions obtained a percentage of 60.94%.